2020
DOI: 10.1186/s12961-020-00628-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining key questions for clinical practice guidelines: a novel approach for developing clinically relevant questions

Abstract: Background There is no standardised protocol for developing clinically relevant guideline questions. We aimed to create such a protocol and to apply it to developing a new guideline. Methods We reviewed international guideline manuals and, through consensus, combined steps for developing clinical questions to produce a best-practice protocol that incorporated qualitative research. The protocol was applied to develop clinical questions for a guideline for general practitioners. Results A best-practice proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…9 A study on guideline development in Australia demonstrated the importance of end-user input to develop focused clinical questions that respond to clinical need. 37 Seminars in Reproductive Medicine © 2022. Thieme.…”
Section: Cpgs In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…9 A study on guideline development in Australia demonstrated the importance of end-user input to develop focused clinical questions that respond to clinical need. 37 Seminars in Reproductive Medicine © 2022. Thieme.…”
Section: Cpgs In Practicementioning
confidence: 99%
“…9 A study on guideline development in Australia demonstrated the importance of end-user input to develop focused clinical questions that respond to clinical need. 37 Such input can help focus evidence-based recommendations thereby increasing their relevance, acceptability, and feasible implementation in clinical practice. Given that the target population for PCC is all people of reproductive age, and that PCC is often delivered opportunistically across different levels of care and even social care, it is necessary to have comprehensive CPGs that answer clinical questions and promote collaboration and provision of high-quality and consistent care.…”
Section: Cpgs In Practicementioning
confidence: 99%
“…The scoping document includes the draft clinical/review questions and provides a clear and transparent structure to guide the GDG. 30 These questions consider efficacy, safety, quality of life, economic information and health services utilisation. The criteria for key review questions to be included in the scope are highlighted in box 1 .…”
Section: A Framework For Developing and Contextualising Guidelines Fo...mentioning
confidence: 99%
“…The source, number, and clarity of clinical questions in guidelines not only determine their recommendations but also have an impact on their dissemination and application, especially if the clinical questions have low relevance to frontline clinicians or the questions are poorly expressed 25 . Clinical questions can be obtained from the current literature (relevant guidelines, systematic reviews, or clinical studies) and from a survey of representative guideline users.…”
Section: Clinical Questionsmentioning
confidence: 99%